Fragmentation challenges amongst construction professional members in South Africa - Papo, Mpho (My University, 2017)
Construction fragmentation remains a major concern amongst professinals through-out project phases in South Africa.The report identifies fragmentation challenges in the context of integration, collaboration, communication and coordination encountered by professinal teams in construction projects. It also investigates whether the intrinsic properties of the construction projects, namely the project size, clients, project locations and project delivery methods, contribute to fragmentatio challenges experienced by the construction professinals. To accomplish this, the study employs mixed method research by using a qualitative tool to capture the raw data from the participants, and analysing the captured data quatitatively. While the results of the study are derived quantitatively, one could not quantitatively measure fragmentation on integration, collaboration, communication and coordination, i.e the results did not translate to weighted fragmentation. However, there are subtle, but enlightening points from the survey that exposed elements of fragmentation challenges faced by the professional team. While some of these challenges seem to lead to natural solutions, it appears most of the may be solved by implementing building information modelling.
A research report submitted to the Faculty of Engineering and the built environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg, 2017
Keywords: Building information modeling; Communication in the building trades; Construction industry--Information resources management